ATTRv MIMICKING CIDP: INSIGHTS FROM TWO GENETICALLY CONFIRMED PATIENTS IN A NATIONAL TOP REFERRAL HOSPITAL - Indrawati, Luh Ari; Hadiweijaya, Antonia; Wiguna, Fikry Ichsan; Parindra, Cakra; Safri, Ahmad Yanuar; Wiratman, Winnugroho; Fadli, Nurul; Harsono, Adrian Ridski; Hakim, Manfaluthy; Octaviana, Fitri (PERDOSNI, 2025)
ATTRv is a treatable autosomal dominant hereditary devastating disease caused by pathogenic variants in TTR gene leading to amyloid deposition in peripheral nerves. TTR stabilizer or gene silencing drugs are able to reduce amyloid formation. It can mimic chronic inflammatory demyelinating polyneuropathy (CIDP) but does not respond to immunotherapy, highlighting the importance of accurate diagnosis. We present two Indonesian male patients initially misdiagnosed with CIDP. The first case developed progressive distal weakness, sensory loss, profound autonomic dysfunction including orthostatic hypotension, erectile dysfunction and significant weight loss. Nerve conduction studies revealed demyelinating sensory neuropathy with mixed motor involvement and autonomic testing showed absent SSR and abnormal HRV. The patient received supportive care, including fludrocortisone for orthostatic hypotension. The second case experienced distal sensory-motor neuropathy with additional features of erectile dysfunction, urinary and fecal incontinence and recurrent painless heel blisters. Nerve conduction studies showed axonal sensorimotor polyneuropathy, and autonomic testing along with SSEP confirmed widespread autonomic and sensory pathway involvement. Serum protein electrophoresis in both cases revealed elevated gamma globulin without monoclonal spikes. Whole exome sequencing in both cases revealed the same pathogenic TTR variant (c.148G>A, p.Val50Met), confirming the diagnosis of ATTRv. CIDP lacks specific biomarkers and can mimic various neuropathies. In this case, distal predominant weakness and profound autonomic dysfunction were red flags for alternative diagnosis, such as ATTRv. Progressive sensory-motor neuropathy, atypical CIDP with autonomic involvement and unexplained weight loss warrant suspicion of ATTRv. Differential diagnoses should include diabetic neuropathy, autoimmune nodopathy, MAG neuropathy and monoclonal gammopathy-associated neuropathies.